Encyclopedia of Industrial Biotechnology 2010
DOI: 10.1002/9780470054581.eib432
|View full text |Cite
|
Sign up to set email alerts
|

Microcarrier Culture

Abstract: Microcarrier culture provides an easily scalable approach to culture of anchorage‐dependent mammalian cells, providing a much higher surface area‐to‐volume ratio compared with roller bottles or flat layer cultivation systems. Microcarriers are also useful for the production of recombinant proteins, particularly to facilitate cell retention in cases where perfusion would be advantageous, for example, low specific productivity or unstable products. Microcarriers provide the cultivation surface that is necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…It has been found that combined cultivation of chondrocytes with microcarriers in a 3D fashion facilitates phenotype maintenance by delivering mechanical stimulation [ 35 ]. Furthermore, MC has the ability to support cell viability and cell adhesion [ 36 ]. Although biomaterials play a role for cell survival and proliferation [ 37 , 38 ], it is questionable whether they also support MSCs differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that combined cultivation of chondrocytes with microcarriers in a 3D fashion facilitates phenotype maintenance by delivering mechanical stimulation [ 35 ]. Furthermore, MC has the ability to support cell viability and cell adhesion [ 36 ]. Although biomaterials play a role for cell survival and proliferation [ 37 , 38 ], it is questionable whether they also support MSCs differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the relevant parameters in the design of the 3D environment is the volume fraction occupied by the microspheres, which is expected to influence cell-material average distance and the dynamics of the system under stirring. This feature is also important for other 3D culture systems, as discussed above in Sections 1.5 and 1.6 (132).…”
Section: Influence Of Volume Fraction Of Acrylic Microspheres On Cell Proliferationmentioning
confidence: 89%